Development, Validation, and Acceptability of the Module in Cebuano Binisaya of Noli Me Tangere.: DEBELOPMENT, BALIDASYON AT AKSEPTABILIDAD NG MODYUL SA SINUGBUANONG BINISAYA NG NOLI ME TANGERE - CALUNSAG, JAMES LLOYD (International Journal of Arts, Sciences and Education, 2025)
This study looks into how well students understand and use Sinugbuanong Binisaya, while also evaluating the effectiveness and acceptability of a Noli Me Tangere module translated into the language of Grade 9 students at Notre Dame Siena Colloege of Polomolok for the academic year 2024–2025. The research followed a descriptive-developmental design, with teachers chosen through Purposive Sampling and students selected through complete enumeration. It focused on assessing the translated text and module in terms of clarity, grammar, rhetorical accuracy, usefulness, and overall appropriateness, while also gauging how both teachers and students felt about the module. The findings showed that students demonstrated a strong command of Sinugbuanong Binisaya, and the module was positively received regarding its objectives, content, and design. There were no significant differences in how teachers and students accepted the module. Overall, the study concluded that teaching Noli Me Tangere in the native language helped improve students' understanding of the text and fostered a deeper appreciation of the culture and language. The study recommends expanding this approach to another schools and local languages in the Philippines, alongside providing additional training for educators to further improve the quality of language-based teaching.